Comparative analysis of 5-year efficacy and outcomes of single anastomosis procedures as revisional surgery for weight regain following sleeve gastrectomy - Asaad F. Salama (17707233) (2023)
Background It is imperative to assess the results of revisional procedures following Sleeve Gastrectomy (SG), given the substantially growing population of patients who experience weight regain within a few years after undergoing this procedure. Objective Examine the comparative effectiveness of the Single Anastomosis Duodeno-Ileal Bypass (SADI-S) and the One Anastomosis Gastric Bypass (OAGB-MGB) as revisional procedures, with respect to their impact on weight loss, resolution of comorbidities, incidence of complications, and rates of reoperation in patients who had weight regain after SG with up to or more than 5 years of follow-up. Setting Hamad General Hospital, Academic tertiary referral center, Qatar. Methods This study retrospectively analyzed a database of patients who underwent the Single Anastomosis Duodeno-Ileal Switch (SADI-S) or the One Anastomosis Gastric Bypass - Mini Gastric Bypass- (OAGB-MGB) as revisional procedures for weight recidivism after a primary Laparoscopic Sleeve Gastrectomy (LSG). The follow-up period was at least 5 years, during which the impact of both procedures on weight loss, comorbidities, nutritional deficiencies, complications, and outcomes were compared. Results The study comprised 91 patients, with 42 and 49 in the SADI-S and OAGB-MGB groups, respectively. Significant weight loss (measured by total weight loss percentage, TWL%) was observed at the 5-year follow-up for the SADI-S group compared to the OAGB-MGB group (30.0 ± 18.4 vs. 19.4 ± 16.3, p = 0.008). Remission of comorbidities, specifically diabetes mellitus and hypertension, was more prevalent in the SADI-S group. Notably, the OAGB-MGB group had a higher incidence of complications (28.6% vs. 21.42%) and reoperations (5 patients vs. 1 in the SADI-S group). No mortality events were reported in either group. Conclusion While both the OAGB-MGB and SADI-S have demonstrated efficacy as revisional procedures for weight regain following SG, the SADI-S exhibits superior outcomes compared to the OAGB-MGB with regard to weight loss, resolution of comorbidities, complication rates, and reoperation rates. Other Information Published in: Surgical Endoscopy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00464-023-10234-3 Additional institutions affiliated with: Heart Hospital - Research Center